From Assimilation to Pluralism and Multiculturalism Policy:State Policy Towards Ethnic Chinese in Indonesia - Wasino Wasino; Saptono Putro; Ananto Aji; Edi Kurniawan; Fitri Amalia Shintasiwi (Paramita: Historical Studies Journal)
Indonesian society inherits plural society of Dutch colonization. One of the major problems is related to the minority ethnicity and its position towards the majority. One of the ethnicities which receives special attention from the government is Chinese. This article is trying to analyse the history of Indonesia Government Policy from Indonesian Independence to Reformasi. The results show that from Indonesian Independence to The New Order era, discrimination politics to Chinese in Indonesia occurs. Chinese is trying to create their image being Indonesian by imitating the majority’s cultural identity or practicing assimilation based on the location where they live. After Reformasi in 1998, the state politics changed by respecting cultures or multicultural society. Therefore, some Chinese identities start to strengthen, but most of them still follow the majority culture.